URGENSI BEKERJA DALAM ALQURAN - Rahmad Kurniawan (POSTGRADUATE OF PALANGKA RAYA STATE ISLAMIC INSTITUTION, 2019)
This article examines the urgency of working based on the Qur'an, it is focused on Surah At-Taubah verse 105 and Surah Al-Jumuah verses 9-11. The method that used in this article is library method; meanwhile normative approach is the approach that used to interpret the Qur'an, specifically. Content analysis and hermeneutics is used to analyzed. The results indicate that the urgency of working in the Qur'an contained in Surah At-Taubah verse 105 concerning the importance of hardworking which will match good results and also emphasizing that the significance of the assessment of work from Allah, the judgment of Rasulullah, and the judgment of believers towards someone's (work) achievements. Furthermore, in Surah Al-Jumuah verses 9-1 declared that if all obligations to Allah have been fulfilled, then someone can back to economic activity or work. Regarding the command to work and worship, when a human works, do not forget worship because not only the world is preferred, but afterlife is prioritized too.